2019
DOI: 10.1186/s12864-019-6277-x
|View full text |Cite
|
Sign up to set email alerts
|

Trans-splicing of mRNAs links gene transcription to translational control regulated by mTOR

Abstract: BackgroundIn phylogenetically diverse organisms, the 5′ ends of a subset of mRNAs are trans-spliced with a spliced leader (SL) RNA. The functions of SL trans-splicing, however, remain largely enigmatic.ResultsWe quantified translation genome-wide in the marine chordate, Oikopleura dioica, under inhibition of mTOR, a central growth regulator. Translation of trans-spliced TOP mRNAs was suppressed, consistent with a role of the SL sequence in nutrient-dependent translational control of growth-related mRNAs. Under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…This is consistent with in vitro biochemical studies which have shown that transcripts beginning with a pyrimidine (C/T) have a lower affinity for eIF4E binding than those starting with a purine (A/G) (Meyuhas and Kahan, 2015;Tamarkin-Ben-Harush et al, 2017). An initial C is a feature of transcripts containing a 5 0 terminal oligo-pyrimidine (TOP) tract, a motif often present in mRNAs encoding the protein synthesis machinery and a target of mTOR-mediated translation control (Meyuhas and Kahan, 2015;Tamarkin-Ben-Harush et al, 2017;Danks et al, 2019). We found that while C has an effect, the overall effect on SE and TE reduction is dominated by mRNAs with the TOP motif (Figure 2G).…”
Section: A B D Csupporting
confidence: 86%
“…This is consistent with in vitro biochemical studies which have shown that transcripts beginning with a pyrimidine (C/T) have a lower affinity for eIF4E binding than those starting with a purine (A/G) (Meyuhas and Kahan, 2015;Tamarkin-Ben-Harush et al, 2017). An initial C is a feature of transcripts containing a 5 0 terminal oligo-pyrimidine (TOP) tract, a motif often present in mRNAs encoding the protein synthesis machinery and a target of mTOR-mediated translation control (Meyuhas and Kahan, 2015;Tamarkin-Ben-Harush et al, 2017;Danks et al, 2019). We found that while C has an effect, the overall effect on SE and TE reduction is dominated by mRNAs with the TOP motif (Figure 2G).…”
Section: A B D Csupporting
confidence: 86%